CULTURAL MEMORY AND MILITARY TRADITION - Stanar, Dragan (Serbian political thought, 2024)
In this article, author aims to offer an in-depth analysis of the place and meaning of cultural memory in the contemporary era of human civilization, observing it from the perspective of the military. By analyzing the phenomenon of cultural memory and cultural trauma, as a necessary element of cultural memory content, author recognizes and lists four key conditions, i.e. criteria that a certain historical trauma must meet in order to constitute cultural trauma. Application of the four conditions to the situation and scenario of soldiers dying in war by the author demonstrates and explains how and why soldiers’ deaths in war cannot in fact constitute cultural trauma, and thus consequently cannot represent the type of suffering and death upon which cultural memory is founded on and upon which collective national identity is built. Author of the paper recognizes the specific role of military tradition as the sole instrument of preservation of memory on soldiers’ sacrifices in war in order to conclude that optimal development, preservation and strengthening of military tradition in all the forms it manifests in constitutes a duty for each and every generation which wishes not only to preserve eternal and dignified memory of those who laid their lives down for their societies and collectives, but also to preserve and maintain the very essence and root of military identity.
Keywords: cultural memory; military tradition; sacrifice; identity; war